The effect of the number of problems of constitutional institutions on the implementation of the public budget: Comparative Study - Aras Hasan Abdulqadir; Kamal Anwar Yaba (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Indeed, the cooperation and coordination among the supreme controlling organs is regarded as an essential guarantee to encounter the frustration of the controlling process of constitutional institutions in the implementation of the public state budget. However, the fundamental challenge behind our research is the lack of cooperation among constitutional institution, due to the combination of their Jurisdiction and overlaps between the supreme controlling agencies, whether by the state authorities themselves through political parties or outside the political structures. Mainly, this research will face an enormous problem in front of the controlling bodies of the constitutional institutions by exercising the controlling process on the implementation of the public state budget and the elimination of financial corruption. Based on the framework of the problems that have been presented in our research according to the analytical method to reveal the challenges facing this control according to the national system, comparing it with the foreign system, and addressing it through the two sections. The first section relates to the content of the diversity of the constitutional structures and the relation to the implementation of the public budget, while the second section relates to the problem of the diversity of the constitutional structures in the French and Lebanese system. As a result of these problems, the lack of the principle of transparency and accountability on the implementation of the public state budget to provide citizens and the conflict of competences between them. Consequently, it leads to the lack of proper control and the spread of financial corruption on the state budget. As a consequence, it is necessary for the national legislature to amend the laws related to the controlling organs in constitutional institutions and unifying the supreme controlling institutions under one legal system, in order to protect public funds (property), and strengthen the rule of law.